2019
DOI: 10.3390/cancers11091334
|View full text |Cite
|
Sign up to set email alerts
|

Triple-Negative Breast Cancer: Current Understanding and Future Therapeutic Breakthrough Targeting Cancer Stemness

Abstract: Triple-negative breast cancer (TNBC) is cancer that tested as negative for estrogen receptors (ER), progesterone receptors (PR), and excess human epidermal growth factor receptor 2 (HER2) protein which accounts for 15%–20% of all breast cancer cases. TNBC is considered to be a poorer prognosis than other types of breast cancer, mainly because it involves more aggressive phenotypes that are similar to stem cell–like cancer cells (cancer stem cell, CSC). Thus, targeted treatment of TNBC remains a major challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
141
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(141 citation statements)
references
References 276 publications
(327 reference statements)
0
141
0
Order By: Relevance
“…As expected, key genes were all overexpressed in BRCA tissues, and the most important was that we found that the expression of key genes in TNBC tissues was quite higher than that in normal tissues. TNBC has a poorer prognosis than other types of breast cancer because of its high degree of malignant phenotypes, which are similar to those of cancer stem cells [20]. We discovered differences in the expression levels of key genes in different subtypes of breast cancer, and 28 of 31 key genes were also upregulated in luminal B tissues compared with luminal A tissues.…”
Section: Discussionmentioning
confidence: 81%
“…As expected, key genes were all overexpressed in BRCA tissues, and the most important was that we found that the expression of key genes in TNBC tissues was quite higher than that in normal tissues. TNBC has a poorer prognosis than other types of breast cancer because of its high degree of malignant phenotypes, which are similar to those of cancer stem cells [20]. We discovered differences in the expression levels of key genes in different subtypes of breast cancer, and 28 of 31 key genes were also upregulated in luminal B tissues compared with luminal A tissues.…”
Section: Discussionmentioning
confidence: 81%
“…Breast cancer is the most common cancer in women worldwide and also the leading cause of cancer death in women (15.0%) [1][2][3]. Within all the possible different subtypes, triple negative breast cancer (TNBC) is the most aggressive subclass and it is characterized by having the worst prognosis 2 of 23 with a high risk of relapse [2,[4][5][6]. TNBCs are characterized by the absence of estrogen and progesterone receptors, as well as by having normal levels of HER2 (human epidermal growth factor receptor 2).…”
Section: Introductionmentioning
confidence: 99%
“…According to the American Cancer Society, approximately 2 million new cases of breast cancer occurred worldwide in 2018 [1]. Major risk factors for breast cancer include genetic mutation, obesity, alcohol consumption, lack of physical activity, red meat consumption, and processed food intake [2][3][4][5]. However, a variety of factors provide prevention of breast cancer occurrence, including sustaining a healthy weight; consuming a diet rich in produce, whole grains, and beans; and limiting consumption of alcohol, red meat, fatty, salty, high sugar foods, and processed foods [6].…”
Section: Introductionmentioning
confidence: 99%